Global change and our common future : papers from a forum - DeFries, Ruth S.; Malone, Thomas F. (National Academy Press, 1989)
The Forum on Global Change and Our Common Future was organized to inform the public about the changes occurring in the global environment and the implications for public policy. This title includes 22 edited presentations from the Forum.